Apresiasi Prosa Novel Negeri 5 Menara: Kajian Nilai Moral sebagai Cermin Pembentukan Karakter Tokoh - Salsabila, Najwa; Injani, Nikita Putri; Setia, Refdi; Abdurahman, Abdurahman (Lembaga Yasin AlSys, 2026)
Moral values in literary works have become a focus in various previous studies, but discussions that specifically position moral values as a reflection of character formation in the novel Negeri 5 Menara remain limited. This study aims to describe the moral values in the novel Negeri 5 Menara by Ahmad Fuadi and to explain their relationship with the formation of the characters’ personalities. This study employed a qualitative approach with a descriptive design based on literary content analysis. The data source of this study was the novel Negeri 5 Menara, while the research data consisted of narratives, dialogues, and events containing moral values. Data were collected through reading and note-taking techniques and were then analyzed through the stages of data reduction, data presentation, interpretation, and conclusion drawing. The results show that the dominant moral values include religiosity, devotion to parents, independence, discipline, hard work, friendship, sincerity, and responsibility. These values play a role in shaping the characters through family conflict, Islamic boarding school life, and friendship relationships. These findings enrich studies of prose appreciation and character education, particularly in understanding literary works as reflective media for the formation of moral values. The conclusion of the study emphasizes the importance of novels as a medium for literature learning that not only provides aesthetic experience but also instills moral values and character in readers.